2007
DOI: 10.1590/s0100-54052007000300012
|View full text |Cite
|
Sign up to set email alerts
|

Incidência de fungos e quantificação de danos em sementes de genótipos de arroz

Abstract: O programa de melhoramento genético de arroz do Instituto Agronômico visa a obtenção de cultivares de arroz altamente produtivas, características tecnológicas desejáveis e resistência a doenças. O presente estudo avaliou genótipos de arroz integrantes dos ensaios comparativos avançados quanto à qualidade sanitária e severidade de manchas nas sementes, peso das sementes por panícula e esterilidade das espiguetas. A qualidade sanitária das sementes variou conforme o sistema de cultivo, com alta incidência dos fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 1 publication
1
13
1
8
Order By: Relevance
“…A infecção de panículas das cultivares IAC 101 e IAC 103 com B. oryzae em condições de campo, no Estado de São Paulo, causou a diminuição em peso e número de grãos, emergência de plântulas e o peso de 100 panículas (10,11).…”
Section: Introductionunclassified
“…A infecção de panículas das cultivares IAC 101 e IAC 103 com B. oryzae em condições de campo, no Estado de São Paulo, causou a diminuição em peso e número de grãos, emergência de plântulas e o peso de 100 panículas (10,11).…”
Section: Introductionunclassified
“…Such differences may be related to a combination of factors related to agronomic and environmental differences. In rice seeds grown in central Brazil, a two-year survey reported B. oryzae at incidence levels averaging 13.6% in the first year and only 1.6% in the second year across 22 rice varieties, suggesting a strong interannual variation (Malavolta et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Sporadic surveys have been conducted to identify Bipolaris associated with rice seeds produced in Brazil (Franco et al, 2001;Farias et al, 2007;Farias et al, 2011) but few attempted to identify Bipolaris at the species level (Malavolta et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Malavolta et al (2007) reported that the severity of grain spots was negatively correlated with panicle weight and the number of filled grains, and positively with the number of void grains and percentage of sterility, thus affecting the main components of rice yield.…”
Section: Methodsmentioning
confidence: 99%